PENGARUH CELEBRITY’S ENDORSMENT DAN WORD OF MOUTH TERHADAP KEPUTUSAN MENONTON FILM NASIONAL (Studi Kasus Pada Penonton Bioskop NSC Sun City Mall Madiun) - Karuniawati Hasanah (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
This study aimed to know the influence of celebrity's endorsment and word of mouth to the decision of the national watch films partially or simultaneously. The preparation of this study using a quantitative approach. based on the nature of this research is a form of associative research with this type of causal relationship. Based on the data obtained, this study is a kind of field research (field research). The study population was moviegoers NSC Sun City Mall Madiun, sample taken 340 respondents with accidental sampling technique. Instrument research on the validity and reliability by looking at the corrected item total correlation and cronbanch's alpha and all declared valid and reliable. Data analysis techniques used in this study by using descriptive analysis techniques and multiple regression.The results showed that the celebrity's endorsment and word of mouth significant effect partially and simultaneously to the national decision at the cinema watching a movie NSC Sun City Mall Madiun. Based on the coefficient of determination (R2) shows that the the effect of celebrity's endorsment and word of mouth to the decision of the national movie in this study explained 51% and the rest is explained factors outside the model.